RNA-sequencing analysis reveals the long noncoding RNA profile in the mouse myopic retina - Li, Yuanjun; Lu, Ying; Du, Kaixuan; Yin, Yewei; Hu, Tu; Fu, Qiuman; Zhang, Yanni; Wen, Dan; Wu, Xiaoying; Xia, Xiaobo (Frontiers in Genetics, 2022)
Aim: Myopia is a prevalent public health problem. The long noncoding RNA (lncRNA) mechanisms for dysregulated retinal signaling in the myopic eye have remained elusive. The aim of this study was to analyze the expression profiles and possible pathogenic roles of lncRNAs in mouse form-deprived myopia (FDM) retinas. Methods: A mouse FDM model was induced and retinas from the FDM right eyes and the contralateral eyes were collected for RNA sequencing. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment, and lncRNA-mRNA coexpression network analyses were conducted to explore the biological functions of the differentially expressed lncRNAs. In addition, the levels of differentially expressed lncRNAs in the myopic retinas were validated by quantitative real-time PCR (qRT–PCR). Fluorescence in situ hybridization (FISH) was used to detect the localization of lncRNAs in mouse retinas. Results: FDM eyes exhibited reduced refraction and increased ocular axial length compared to control fellow eyes. RNA sequencing revealed that there were 655 differentially expressed lncRNAs between the FDM and control retinas. Functional enrichment analysis indicated that the differentially expressed RNAs were mostly enriched in cellular processes, cytokine-cytokine receptor interactions, retinol metabolism, and rhythmic processes. Differentially expressed lncRNAs were validated by qRT–PCR. Additionally, RNA FISH showed that XR_384718.4 (Gm35369) localized in the ganglion cell (GCL) and inner nuclear layers (INL). Conclusion: This study identified the differential expression profiles of lncRNAs in myopic mouse retinas. Our results provide scientific evidence for investigations of myopia and the development of putative interventions in the future.